Heterostructure of amorphous nickel boride anchored 2D-layered cobalt selenide nanosheets as a disposable strip sensor for detection of toxic pollutant 5-nitroquinoline in aquatic samples. (20th February 2023) - Sukanya, Ramaraj; Karthik, Raj; Mohandoss, Sonaimuthu; Hasan, Mahmudul; Shim, Jae-Jin; Lee, Yong Rok
Abstract: The development of disposable electrode-based sensors is of great importance for the electrochemical monitoring of toxic pollutants in wastewater systems, which are often present and mutually inhibiting during sample detection. In this work, a distinctive approach was taken to use an electrochemical heterostructure sensor with chemically reduced nickel boride (Ni3 B) nanoparticles anchored in two-dimensional (2D) layered cobalt selenide (CoSe) nanosheets. The prepared hybrid structure (2D CoSe/Ni3 B) enables large active sites and a strong synergistic effect between nanostructures to improve the electrocatalytic activity in the detection of water pollutant 5-nitroquinoline (5-NQ) with a disposable screen-printed carbon electrode (SPCE). The 2D CoSe/Ni3 B/SPCE exhibits a reduction peak potential of −0.63 V for 5-NQ, with an increased reduction peak current compared to that of other electrodes. The fabricated disposable strip electrode is suitable for the electrochemical testing of pollutants. The proposed hybrid 2D CoSe/Ni3 B/SPCE disposable sensor showed a wide linear range of 0.2–378 μM and a low detection limit of 0.042 μM for 5-NQ. The developed 2D CoSe/Ni3 B hybrid nanostructure-based disposable sensor efficiently detects 5-NQ in hazardous water contaminants by voltammetric analysis and showed acceptable recoveries. Based on the results, it is believed that the proposed work provides a clear idea for the fabrication of transition metal-based metal boride and selenide heterostructures with excellent catalytic activity for the electrochemical detection of various pollutants in real-time monitoring. Graphical abstract: Image 1 Highlights: 2D-CoSe/Ni3 B hybrid was prepared by a simple synthesis method. The hybrid shows excellent electrocatalytic activity for the detection of 5-NQ. The strong synergistic effect between Ni3 B and CoSe shows higher catalytic activity. The 2D-CoSe/Ni3 B/SPCE sensor shows a very low LOD (0.042 μM). The 2D-CoSe/Ni3 B/SPCE sensor has good recovery results for real-time analysis.